Arsitektur Jaringan telekomunikasi - Nasrudin Nasrudin; Fitriani Fitriani; Sukira Sukira; Didik Aribowo (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
The development of technology in this world is increasingly growing rapidly, one of which is in the development of cellular telecommunications. 5G technology is the name of the 5th generation of mobile communication development, whose standards exceed those of the 4G generation. The literature review in this journal includes network architecture, LAN, CPU, UE, and MCC. The research method used by the author is descriptive research method. The results are that the use of cloud computing at the edge of the network will make the signal from 5G faster than 4G, because the data has been stored and the more users who use it will increase the speed even more and shortening the signaling delay is used to avoid signal transmission from SCeNBces to centralized SCM.